Cymerus™ iPSC-MSCs significantly prolong survival in a pre-clinical, humanized mouse model of Graft-vs-host disease - E. Ilker Ozay; Jyothi Vijayaraghavan; Gabriela Gonzalez-Perez; Sudarvili Shanthalingam; Heather L. Sherman; Daniel T. Garrigan, Jr.; Karthik Chandiran; Joe A. Torres; Barbara A. Osborne; Gregory N. Tew; Igor I. Slukvin; Ross A. Macdonald; et al. (Stem Cell Research, 2019)
The immune-mediated tissue destruction of graft-vs-host disease (GvHD) remains a major barrier to greater use of hematopoietic stem cell transplantation (HSCT). Mesenchymal stem cells (MSCs) have intrinsic immunosuppressive qualities and are being actively investigated as a therapeutic strategy for treating GvHD. We characterized Cymerus™ MSCs, which are derived from adult, induced pluripotent stem cells (iPSCs), and show they display surface markers and tri-lineage differentiation consistent with MSCs isolated from bone marrow (BM). Administering iPSC-MSCs altered phosphorylation and cellular localization of the T cell-specific kinase, Protein Kinase C theta (PKCθ), attenuated disease severity, and prolonged survival in a humanized mouse model of GvHD. Finally, we evaluated a constellation of pro-inflammatory molecules on circulating PBMCs that correlated closely with disease progression and which may serve as biomarkers to monitor therapeutic response. Altogether, our data suggest Cymerus iPSC-MSCs offer the potential for an off-the-shelf, cell-based therapy to treat GvHD. Keywords: PKCθ, Graft-vs-host disease, Mesenchymal stem cell, Induced pluripotent stem cell, Humanized mouse model